2014
DOI: 10.1128/jb.00061-14
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of BCAM0224, a Multifunctional Trimeric Autotransporter from the Human Pathogen Burkholderia cenocepacia

Abstract: Members of the trimeric autotransporter adhesin (TAA) family play a crucial role in adhesion of Gram-negative pathogens to host cells. Moreover, these proteins are multifunctional virulence factors involved in several other biological traits, including invasion into host cells and evasion of the host immune system. In cystic fibrosis epidemic Burkholderia cenocepacia strain J2315, we identified a unique TAA (BCAM0224)-encoding gene, previously described as being implicated in virulence. Here, we characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 51 publications
2
35
0
Order By: Relevance
“…A 22-kDa cable pilus protein was identified as an adhesin; however, it is expressed in only a subset of B. cenocepacia strains, i.e., piliated strains of the subgroup IIIA lineage only (30), and is not expressed in the more frequently acquired species B. multivorans. More recently, Mil-Homens et al identified two closely related trimeric autotransporters that are involved in B. cenocepacia adhesion to lung epithelial cells (31,32). We have developed a proteomics approach to identify other bacterial proteins that are involved in the attachment of Bcc to lung epithelial cells in vitro by probing two-dimensional (2D) blots of bacterial proteins with epithelial cells.…”
mentioning
confidence: 99%
“…A 22-kDa cable pilus protein was identified as an adhesin; however, it is expressed in only a subset of B. cenocepacia strains, i.e., piliated strains of the subgroup IIIA lineage only (30), and is not expressed in the more frequently acquired species B. multivorans. More recently, Mil-Homens et al identified two closely related trimeric autotransporters that are involved in B. cenocepacia adhesion to lung epithelial cells (31,32). We have developed a proteomics approach to identify other bacterial proteins that are involved in the attachment of Bcc to lung epithelial cells in vitro by probing two-dimensional (2D) blots of bacterial proteins with epithelial cells.…”
mentioning
confidence: 99%
“…(Supplementary Table 5). BcenGI15 encodes a gene for auto transporter adhesion having YadA domain known to be important in the pathogenesis related functions like adherence, biofilm formation, invasion, survival within eukaryotic cells, serum resistance, and cytotoxicity (Mil-Homens and Fialho, 2011; Mil-Homens et al, 2014). Four genes of BcenGI15 encode ankyrin repeat proteins (CD0024) that are abundant in eukaryotes and play a role in protein–protein interactions (Li et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Although some adhesin proteins of B. cenocepacia have been implicated in attachment to epithelial cells (46,58,59), no studies on the putative adhesins of B. contaminans IST408 have been done. Previous expression profiling (under growth conditions dissimilar from the ones tested here) of the bceF mutant compared to the IST408 parental strain showed decreased ex- pression of a putative autotransporter adhesin homologue to BCAS0321 of B. cenocepacia J2315 and at least eight genes encoding putative outer membrane porins (7).…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the adhesion experiment, coverslips with cells were washed with PBS. Immunostaining experiments were performed as previously described (46). For these experiments, samples were fixed with 3.7% (vol/vol) formaldehyde for 20 min, quenched with 50 mM NH 4 Cl for 10 min, immersed in 0.2% (vol/vol) Triton X-100 for 5 min, and saturated with 5% (wt/vol) bovine serum albumin (BSA) during 30 min.…”
Section: Methodsmentioning
confidence: 99%